Driver Behaviour Intention to Speeding at School Zone Based on Theory of Planned Behaviour - Abdul Rahman, Abdul Hadi; Kamaruddin Ambak (Recent Trends in Civil Engineering and Built Environment, 2021)
Road safety is an important issue that should be emphasized especially when in the school district as it has a high risk of being involved in serious injuries and fatalities during public conflicts in school and car drivers. This study analyzes the relationship between the variables of the Theory of Planned Behavior (TPB) and the tendency of car drivers to speed in school zone. A total of 200 questionnaires were distributed randomly to respondents in the study area and observations are conducted to collect were on driver characteristics in the school district at Batu Pahat area but due to pandemic of Covid-19 the observation was conduct by analyse the respondent data given via Online (Google form). The questionnaire consisted of three sections and is based on the TPB model and data was analysed using descriptive, correlation, and regression analysis. From the observation carried out, the majority of drivers who comply with the speed limit drive have any conflicts with other road users, but there are a few near-miss accidents observed involving people under 30 years of age. Beside, data analysis shows that the perceived behavioural control was influence the intention of driver to speed at school zone. Finally, some recommendation suggested to reduce the speeding intention at school zone such as add humps in school areas.